REFUSAL OF FOREIGNERS TO INDONESIA THROUGH IMMIGRATION CHECKPOINTS AT INTERNATIONAL AIRPORTS: AN ABSOLUTE SOVEREIGNTY - Ridwan Arifin (Jurnal Ilmiah Kajian Keimigrasian, 2018)
This paper is to discuss the implementation of denied entry person into Indonesia in term of a national sovereignty. The security approach and selective policy are two main features in analyzing the provisions and practice of refusing an inadmissible person for immigration reasons at Immigration border controls across Indonesian international airports. Relating to law enforcement at borders, this is also to identify how immigration officers play important roles subject to Indonesian immigration policy and laws.